Determining the cultural and social drivers in attracting the creative class and investors in metropolises of Iran (case example, Mashhad) - Rostam Saberifar (جغرافیا و توسعه, 2023)
One of the main factors in increasing income and employment, as the most important pillar of livable cities, is attracting the creative class and investors. Implementing innovative plans and making basic investments in line with sustainable development requires many conditions and fields, one of the most important of which is the availability of cultural and social fields. But so far, this field and categories have been less in the focus of attention. For this purpose, in this study, an attempt was made to take into account the role and position of culture and social contexts in attracting investors to the city of Mashhad by using the descriptive-analytical method. For this purpose, emphasis was mainly placed on the main drivers of this field. To reach this goal, the required information was collected from library and field sources. In the field part, the research sample included 30 qualified people in this field, who were selected by purposeful sampling. Micmac software was also used for data analysis. The results showed that the factors that influence the attraction of the creative class and investors and the increase of targeted investments in the city of Mashhad are: Investment in research and development, laws and regulations, number of resident foreigners, information and communication technology, appropriate financing, flight destinations and active airlines, rate of invention and innovation, level of literacy and education, performance evaluation and reward system, financial policies, flexible financial systems, scientific and technical exchanges and interaction between university and industry.